LED Lighting Strategies Affect Physiology and Resilience to Pathogens and Pests in Eggplant (Solanum melongena L.) - Anja Dieleman, J.; Marjolein Kruidhof, H.; Weerheim, Kees; Leiss, Kirsten (Frontiers in Plant Science, 2021)
Over the last decade, LED lighting has gained considerable interest as an energy efficient supplemental light source in greenhouse horticulture, that can change rapidly in intensity and spectral composition. Spectral composition does not only affect crop physiology, but may also affect the biology of pathogens, pests and their natural enemies, both directly and indirectly through an impact on induced plant resistance. In this study, we investigated the effects of light spectrum against a background of sunlight on growth and development of Solanum melongena. These effects were related to the spectral effects on the establishment of populations of the predatory mite Amblyseius swirskii and plant resilience against thrips, the biotrophic fungus powdery mildew and the necrotrophic fungus botrytis. The effects of a reduced red to far-red (R:FR) ratio were studied under two ratios of blue to red light. Far-red light was either supplied additionally to the photosynthetic photon flux density (PPFD), or partially replaced PPFD, while maintaining total photon flux density (PFD). Effects of white light or additional UV-B light on plant resilience was tested, compared to the reference (5% blue, 5% green, 90% red light). Plant biomass in the vegetative phase increased when additional far-red light was supplied. Stem length increased with far-red, irrespective of PPFD and the percentage of blue light. In the generative phase, total shoot biomass and fruit fresh weights were higher under additional far-red light, followed by the treatments where far-red partly replaced PPFD. Far-red light increased biomass partitioning into the fruits, at the expense of the leaves. There were no differences in population growth of Amblyseius swirskii mites between light treatments, nor had light treatment an effect on the vertical distribution of these predatory mites in the plants. The treatments with additional far-red light reduced the infection rate of powdery mildew, but increased botrytis infection. These differences might be due to the plant defenses acting against these pathogens evolving from two different regulatory pathways. These results show that positive effects of altered spectral compositions on physiological responses were only moderately compensated by increased susceptibility to fungal pathogens, which offers perspective for a sustainable greenhouse horticulture.